Rabies virus uniquely reprograms the transcriptome of human monocyte-derived macrophages - Embregts, Carmen W.E.; Wentzel, Annelieke S.; Dekker, Alexander T. den; van IJcken, Wilfred F.J.; Stadhouders, Ralph; GeurtsvanKessel, Corine H. (Frontiers in Cellular and Infection Microbiology, 2023)
Macrophages are amongst the first immune cells that encounter rabies virus (RABV) at virus entry sites. Activation of macrophages is essential for the onset of a potent immune response, but insights into the effects of RABV on macrophage activation are scarce. In this study we performed high-throughput sequencing on RNA extracted from macrophages that were exposed to RABV for 48 hours, and compared their transcriptional profiles to that of non-polarized macrophages (M0), and macrophages polarized towards the canonical M1, M2a and M2c phenotypes. Our analysis revealed that RABV-stimulated macrophages show high expression of several M1, M2a and M2c signature genes. Apart from their partial resemblance to these phenotypes, unbiased clustering analysis revealed that RABV induces a unique and distinct polarization program. Closer examination revealed that RABV induced multiple pathways related to the interferon- and antiviral response, which were not induced under other classical polarization strategies. Surprisingly, our data show that RABV induces an activated rather than a fully suppressed macrophage phenotype, triggering virus-induced activation and polarization. This includes multiple genes with known antiviral (e.g. APOBEC3A, IFIT/OAS/TRIM genes), which may play a role in anti-RABV immunity.